The Politics and strategy of nuclear weapons in the Middle East : opacity, theory, and reality, 1960-1991 : an Israeli perspective - Aronson, Shlomo, 1936-; Brosh, Oded. (Albany : State University of New York Press, 1992)
Annotation Aronson (political science, Hebrew U., Jerusalem) explains Israel's acquisition and political use of nuclear weapons as a central factor in its foreign policy over the last three decades, emphasizing Israeli and Arab perceptions of each other, the changing roles of the US and USSR, and the nuclear element in the Gulf War and the Intifada. Paper edition (unseen), $19.95. Annotation copyrighted by Book News, Inc., Portland, OR.
Strategy, history, and politics -- The American paradigm and early efforts to limit proliferation -- The Israeli paradigm: American controlled opacity? -- American intervention -- The 1967 war -- The road to the Yom Kippur War -- The walls of Jericho -- Sadat's peace -- The doctrine of opaque nuclear monopoly -- Lebanon and the demise of the Begin-Sharon Cabinet -- From Lebanon to the Intifada -- The rebirth of Pan-Arabism? -- India, Pakistan, North Korea, Algeria, Iran, and the rest.
Includes bibliographical references (pages 357-369) and indexes.
Print version record.
English.
JSTOR
Keywords: Middle East -- Military policy; Israel -- Military policy; Nuclear weapons -- Middle East; Nuclear weapons -- Israel; Nuclear nonproliferation; Armes nucléaires -- Moyen-Orient.; Armes nucléaires -- Israël.; Non-prolifération nucléaire.; Israël -- Politique militaire; Moyen-Orient -- Politique militaire; TECHNOLOGY & ENGINEERING -- Military Science; HISTORY -- Military -- Other; Military policy; Nuclear nonproliferation; Nuclear weapons; Israel; Middle East